2017
DOI: 10.1016/j.cryobiol.2016.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Fertility response of artificial insemination methods in sheep with fresh and frozen-thawed semen

Abstract: The aim of this study was to evaluate the fertility response of artificial insemination (AI) methods with fresh and frozen sperm in sheep. In experiment 1, one hundred and fifty fat tailed Zandi ewes were assigned into 3 equal groups and inseminated with three AI methods consisting of vaginal, laparoscopic and trans-cervical AI with fresh semen. In experiment 2, a factorial study (3 AI methods × 2 extenders) was used to analyze the effects of three AI methods and two freezing extenders containing soybean lecit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 31 publications
3
32
0
2
Order By: Relevance
“…With frozen‐thawed semen, cervical insemination rates are generally low and are obtained from unrepresentative experimental studies (few inseminations) under very diverse conditions, which makes it difficult to transfer this practice to a productive sector: 4% (Masoudi et al., ), 28% (Gil, Rodriguez‐Irazoqui, Lundeheim, Söderquist, & Rodríguez‐Martínez, ) and 13% (Byrne et al., ). Exceptionally, Paulenz et al.…”
Section: Cervical Insemination: a Classic To Improvementioning
confidence: 99%
See 2 more Smart Citations
“…With frozen‐thawed semen, cervical insemination rates are generally low and are obtained from unrepresentative experimental studies (few inseminations) under very diverse conditions, which makes it difficult to transfer this practice to a productive sector: 4% (Masoudi et al., ), 28% (Gil, Rodriguez‐Irazoqui, Lundeheim, Söderquist, & Rodríguez‐Martínez, ) and 13% (Byrne et al., ). Exceptionally, Paulenz et al.…”
Section: Cervical Insemination: a Classic To Improvementioning
confidence: 99%
“…The membrane protectors classically used to preserve refrigerated sperm have been skim milk and egg yolk. For ovine semen stored for short periods (<12 hr – 15°C), milk: 66% (Paulenz, Söderquist, Ådnøy, Fossen, & Berg, ), egg yolk: 56% (Masoudi et al., ) or both together 70% (Donovan et al., ) offer good fertility results.…”
Section: Cervical Insemination: a Classic To Improvementioning
confidence: 99%
See 1 more Smart Citation
“…This answer may be explained by effects of oxytocin that initiates collagenolytic enzyme process resulting in cervical dilation [19]. Previous studies showed that E 2 +OT or only OT [13,[20][21][22] caused cervical dilation in ewes. It has been proven that 400 IU OT led to dilation of cervix, but the injection of this amount of hormone right before the insemination may have some problems.…”
Section: Discussionmentioning
confidence: 99%
“…Semen cryopreservation has allowed specific opportunities for conservation of genetic resources through sperm banks, guarantee of a constant commercial supply of semen, and collaboration in breed improvement programs by artificial insemination (Bucak et al, 2007;Masoudi et al, 2017). Semen cryopreservation may lead to oxidative, chemical and physical damages on sperm membrane leading to reduction of sperm viability and fertility (Evans et al, 1987;Watson, 2000;Emamverdi et al, 2014;Najafi et al, 2014a;Sarıözkan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%